Self‐expandable valve‐in‐valve treatment for failing sutureless aortic bioprosthesis. Issue 2 (25th November 2019) - Belluschi, Igor; Buzzatti, Nicola; Blasio, Andrea; Romano, Vittorio; De Bonis, Michele; Castiglioni, Alessandro; Montorfano, Matteo; Alfieri, Ottavio
Abstract: Aortic valve replacement still represents the gold standard treatment for severe symptomatic aortic stenosis. Sutureless bioprostheses have been so far developed to enhance the minimally invasive approach, resulting in a reduction of cross‐clamp time. Even if the first implantation was carried out more than 10 years ago, some cases of valve degeneration treated with balloon‐expandable valve‐in‐valve procedures have been previously described in the literature. Here, we present a case of early sutureless valve degeneration resulting in severe aortic regurgitation. After careful evaluation of the patient's comorbidities, a successful valve‐in‐valve was finally performed using a self‐expandable transcatheter prosthesis. A wide discussion of the Heart Team decision‐making process and of the technical aspects has been addressed.